Teacher's Strategic Approach in Handling Unruly Students: An Examination of the Story of Prophet Moses - Listiana, Anggun Afri (TA`DIBUNA, 2025)
Student delinquency is increasingly prevalent and has an impact on conflicts between students and teachers. This is evidenced by the many cases of teacher violence against students who commit offenses. This study explores the teacher's approach strategy in dealing with delinquent students through an examination of the story of Prophet Moses. This study uses a qualitative method with a library research approach. The purpose of this study is to identify the educational principles and approaches of Prophet Moses that are relevant in dealing with students' negative behavior, analyzing how strategies adapted from the story of Prophet Moses to help teachers approach unruly students. This study found educational strategies based on educational principles taken from the story of Prophet Moses, namely, a gentle and wise approach, teaching with patience by giving students the opportunity to experiment to feel failure, exemplary approach, firm but fair attitude, strengthening prayer and hope. These principles can be applied through various learning strategies, including active listening, project-based learning, differentiated learning, coaching and mentoring approaches, discussions, case studies, and reflection. The findings underscore the importance of appropriate approaches by teachers in dealing with students' negative behaviors to create a more conducive learning environment, build positive relationships, and help students' character and academic development.